Awareness Of Cervical Cancer Screening Among Paramedical Staff and Students in An Institution of Northern India - Gupta, Manisha; Yadav, Megha; Agarwal, Neelima; Arora, Raksha (National Journal of Community Medicine, 2013)
Introduction: Cervical cancer is one of the leading causes of morbidity and mortality worldwide. Most women with cervical cancer present with advanced disease, resulting in low cure rates. Factors contributing to high burden of disease and advanced stage at presentation include poor knowledge about the disease furthermore and lack of screening among general population. Objective: To assess the knowledge and awareness of cervical cancer and explore attitudes and practices of Pap smear screening among paramedical staff and students in Santosh Medical College & Hospitals, Ghaziabad. Methods: A pretested self administered questionnaire based survey was done on 500 paramedical staff and students of Santosh Medical College & Hospitals, Ghaziabad, UP containing simple questions about demographics, knowledge about cervical cancer, its risk factors, screening techniques, attitudes towards cervical cancer screening and its practices. Results: In this study, about 20% were not aware of cervical cancer as a disease.19% knew that Pap smear is used for detection of preinvasive cervical cancer. O About 80% of subjects did not know that it was possible to detect cervical cancer early nor were they aware of different screening methods like Paps smear and had limited understanding of the types of cervical cancer screening techniques and poor disposition towards undergoing cervical cancer screening. 30% of the respondents knew about HPV Vaccine. Conclusion: This study serves to highlight that majority of paramedical staff was ill equipped with knowledge concerning cervical cancer.